Heterogeneous genome divergence, differential introgression, and the origin and structure of hybrid zones. Issue 11 (17th March 2016) - Harrison, Richard G.; Larson, Erica L.
Abstract: Hybrid zones have been promoted as windows on the evolutionary process and as laboratories for studying divergence and speciation. Patterns of divergence between hybridizing species can now be characterized on a genomewide scale, and recent genome scans have focused on the presence of 'islands' of divergence. Patterns of heterogeneous genomic divergence may reflect differential introgression following secondary contact and provide insights into which genome regions contribute to local adaptation, hybrid unfitness and positive assortative mating. However, heterogeneous genome divergence can also arise in the absence of any gene flow, as a result of variation in selection and recombination across the genome. We suggest that to understand hybrid zone origins and dynamics, it is essential to distinguish between genome regions that are divergent between pure parental populations and regions that show restricted introgression where these populations interact in hybrid zones. The latter, more so than the former, reveal the likely genetic architecture of reproductive isolation. Mosaic hybrid zones, because of their complex structure and multiple contacts, are particularly good subjects for distinguishing primary intergradation from secondary contact. Comparisons among independent hybrid zones or transects that involve the 'same' species pair can also help to distinguish between divergence with gene flow and secondary contact. However, data from replicate hybrid zones or replicate transects do not reveal consistent patterns; in a few cases, patterns of introgression are similar across independent transects, but for many taxa, there is distinct lack of concordance, presumably due to variation in environmental context and/or variation in the genetics of the interacting populations.